Dimensions of Security in the Kurdistan Region from the Perspective of the Copenhagen School: Threat and Risk Assessment - mina khan, سیروان; Majid Khalil, هیوا (Zanco Journal of Law and Politics گۆڤاری زانكۆ بۆ یاساو رامیاری, 2025)
This research endeavors to comprehensively analyze the security issues of the Kurdistan Region within the theoretical framework of the Copenhagen School. The Copenhagen School identifies five primary security sectors: political, economic, societal, military, and environmental security. This theoretical framework provides the opportunity to discuss threats and latent dangers within the context of security issues in a comprehensive and integrated manner. The Kurdistan Region has faced several crises and sensitive issues since 2014 that have had negative impacts on all aspects of security. The main research question of this study is: What are the principal threats that have endangered each of the security sectors of the Kurdistan Region? The primary hypothesis posits that the main issues of security dimensions manifested in the Kurdistan Region are evident across all five sectors, and these security threats have negative effects on the survival and continuity of the Kurdistan Region. The research methodology relies on a qualitative approach through descriptive-analytical analysis and case study analysis of the Kurdistan Region as a distinct unit.